2021
DOI: 10.1155/2021/5536137
|View full text |Cite
|
Sign up to set email alerts
|

A Numerical Investigation of the Deformation Mechanism of a Large Metro Station Foundation Pit under the Influence of Hydromechanical Processes

Abstract: Considering the unique conditions of deep and large subway foundation pit excavation affected by heavy rainfall in soil-rock composite strata, this paper employs finite element numerical simulation methods to study foundation pit instability under the influence of heavy rainfall. According to the hydraulic coupling conditions caused by rainfall, a fluid-solid coupling numerical model for a deep and large subway foundation pit in soil-rock composite strata is established in this paper. By selecting the Anshan r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…where q is the magnitude of rainfall intensity; t p � (θ s − θ i )S f /q(q/k s − 1); k s is the saturated permeability coefficient of unsaturated slope soils; and S f is the substrate potential head of the unwetted layer relative to the saturated layer. e substrate potential head is taken as half of the water potential corresponding to the inlet pressure value of the soil [17,20,29].…”
Section: Study Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…where q is the magnitude of rainfall intensity; t p � (θ s − θ i )S f /q(q/k s − 1); k s is the saturated permeability coefficient of unsaturated slope soils; and S f is the substrate potential head of the unwetted layer relative to the saturated layer. e substrate potential head is taken as half of the water potential corresponding to the inlet pressure value of the soil [17,20,29].…”
Section: Study Methodsmentioning
confidence: 99%
“…Richa et al [16] found an analytical expression for the effective saturated hydraulic conductivity and analyzed the infiltration rate of unsaturated soils and the evolutionary characteristics of soil surface moisture under rainfall conditions. Wang et al [17] established a numerical model of flow-solid coupling on the slope of foundation pits with soil-rock composite strata to analyze the change law of hydraulic coupling caused by rainfall. Guo et al [18] analyzed the effect of inhomogeneous initial water content on the improved GA model in conjunction with the field monitoring results.…”
Section: Introductionmentioning
confidence: 99%
“…e following conclusions can be drawn from Table 5 and Figure 7: (1) FOS of foundation pit vertical soil sidewall decreases with the increase of soil wall excavation height. According to the criterion of F ST �1.35, Hs 0 is 6.92 m. (2) According to the relationship between Hs and Hs 0 , the stable state of the vertical soil wall can be quickly determined: when Hs ≤ Hs 0 , soil wall excavation meets the self-stability requirements. On the contrary, when Hs > Hs 0 , soil wall excavation cannot meet the requirements of self-stability.…”
Section: Study On the Self-stabilizing Height Of Vertical Soilmentioning
confidence: 99%
“…With the accelerating process of urbanization in China, a type of deep foundation pit whose bottom is above the interface between soil stratum and rock stratum comes into being. e unique feature of this deep foundation pit type is that the strata within its excavation depth are composed of soil and rock from top to bottom, and the difference of the main mechanical parameters such as cohesion and elastic modulus between the two strata is almost thousands of times, such as Wusi Square Station foundation pit of Qingdao Metro Line 3 [1], Anshan Road Station foundation pit of Qingdao Metro Line 4 [2,3], and Chashan station foundation pit of Shenzhen Metro Line 7 [4]. In this paper, this type of deep foundation pit is uniformly called deep foundation pit in the binary strata of upper soil and lower rock.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the excavation of foundation pits always induced settlement of the surrounding buildings and influenced adjacent subway tunnels [1][2][3]. There are many factors, such as excavation unloading [4][5][6], groundwater drawdown [7][8][9], unloading modulus, excavation method [10,11], space-time effect [12,13], and other factors that are related to the surrounding deformation of the foundation pit. These factors pose great challenges to the safety of the surrounding environment and the foundation pit itself.…”
Section: Introductionmentioning
confidence: 99%